2009
DOI: 10.1177/1354068808099978
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Level Relations in Political Parties

Abstract: Most political parties operate on several territorial levels, but we have only limited theoretical understanding of multi-level party dynamics. This article presents a delegation framework for studying the interaction between the national leadership and regional branches in state-wide parties. Assuming a principal—agent relationship, the national leadership can obtain benefits from delegating tasks to a regional branch, but also faces possible costs in doing this. The rules and conventions regulating the multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 42 publications
0
44
0
6
Order By: Relevance
“…Different authors have analyzed the effects of sub-state elections in forcing nation-wide political parties to "regionalize" their structure and tactics, in Spain (Pallárés and Keating, 2003;Libbrecht et al, 2011), as well as in other countries (Houten, 2009;Hopkin and Bradbury, 2006;Chhibber and Kollman, 2004;Brancati, 2008). Thus, whether it is due to the political manipulation of regional political elites or to the regionalization of welfare regimes (Mota, 1998: 5;Díez, 1999;Martínez-Herrera, 2002: 424-6;McEwen and Moreno, 2005), decentralization has been related to the development of regional identities at the cost of state-wide national identities .…”
Section: Theorizing and Modeling The Influence Of Country-level Variamentioning
confidence: 99%
“…Different authors have analyzed the effects of sub-state elections in forcing nation-wide political parties to "regionalize" their structure and tactics, in Spain (Pallárés and Keating, 2003;Libbrecht et al, 2011), as well as in other countries (Houten, 2009;Hopkin and Bradbury, 2006;Chhibber and Kollman, 2004;Brancati, 2008). Thus, whether it is due to the political manipulation of regional political elites or to the regionalization of welfare regimes (Mota, 1998: 5;Díez, 1999;Martínez-Herrera, 2002: 424-6;McEwen and Moreno, 2005), decentralization has been related to the development of regional identities at the cost of state-wide national identities .…”
Section: Theorizing and Modeling The Influence Of Country-level Variamentioning
confidence: 99%
“…For instance, whilst a measure of policy-making autonomy over areas of regional competence is desirable for sub-national parties, statewide parties tend to be mindful of the potential party programme incoherence that can occur as a result. There is a tension between tailoring policies to suit local needs and party competition on the one hand, and maintaining a strong national party identity on the other (van Houten, 2009;Carty, 2004). Policy divergence poses awkward questions for the both the party"s core and its regions.…”
Section: Adapting To the Regional/national Dilemmamentioning
confidence: 99%
“…Este proceso ha sido paralelo a la consolidación electoral de partidos de ámbito no estatal (PANE) en regiones donde anteriormente esta dimensión no era significativa. Diversos autores han demostrado, tanto para el caso de España (Pallarés y Keating, 2003; Libbrecht, Maddens y Swenden, 2011) como para otros países, que los contextos multinivel generan competencia entre los niveles centrales y regionales de los partidos, forzándolos a modificar sus estructuras y sus tácticas, regionalizándolas (Houten, 2009; Hopkin y Bradbury, 2006; Chhibber y Kollman, 2004;Brancati, 2008). La evidencia con la que contamos indica que entre la ciudadanía, «el proceso de institucionalización [de las comunidades autónomas] ha requerido la producción de nuevos sím-bolos y referentes políticos comunitarios que han generado nuevas lealtades políticas e identidades colectivas» (Mota Consejero, 1 El proyecto de investigación «Negotiating Spain: The shifting boundaries between "nation", "nationality" and "region"» en que se basa esta nota ha sido posible gracias a la financiación de la Comisión Europea (FP7-PEOPLE-2013-IEF, Grant Agreement Number 621761).…”
unclassified
“…This process has been parallel to the electoral consolidation of Non-State-Wide Parties (NSWP) in regions where they were previously not significant. Several scholars have shown that multi-level contexts generate competition between the central and regional levels of parties, forcing them to modify their structures and tactics, in order to regionalise them both in the case of Spain (Pallarés and Keating, 2003;Libbrecht, Maddens and Swenden, 2011), as well as for other countries (Houten, 2009;Hopkin and Bradbury, 2006;Chhibber and Kollman, 2004;Brancati, 2008). The evidence collected in this study indicates that "the process of institutionalisation [of the Autonomous Regions] has required producing new symbols and political reference points in the Autonomous Regions that have generated new political 1 The research project entitled "Negotiating Spain: The shifting boundaries between 'nation', 'nationality' and 'region' " on which this paper is based was possible thanks to the funding from the European Commission (FP7-PEOPLE-2013-IEF, Grant Agreement Number 621761).…”
Section: Introductionmentioning
confidence: 99%